Limited Responsiveness of Chloroplast Gene Expression during Acclimation to High Light in Tobacco . Issue 1 (21st October 2019) - Schuster, Maja; Gao, Yang; Schöttler, Mark Aurel; Bock, Ralph; Zoschke, Reimo
Abstract : Short-, medium-, and long-term acclimation of tobacco seedlings to increased light intensities involves only minor adjustments of the chloroplast transcriptome and protein translation. Abstract: Acclimation to changing light intensities poses major challenges to plant metabolism and has been shown to involve regulatory adjustments in chloroplast gene expression. However, this regulation has not been examined at a plastid genome-wide level and for many genes, it is unknown whether their expression responds to altered light intensities. Here, we applied comparative ribosome profiling and transcriptomic experiments to analyze changes in chloroplast transcript accumulation and translation in leaves of tobacco ( Nicotiana tabacum ) seedlings after transfer from moderate light to physiological high light. Our time-course data revealed almost unaltered chloroplast transcript levels and only mild changes in ribosome occupancy during 2 d of high light exposure. Ribosome occupancy on the psbA mRNA (encoding the D1 reaction center protein of PSII) increased and that on the petG transcript decreased slightly after high light treatment. Transfer from moderate light to high light did not induce substantial alterations in ribosome pausing. Transfer experiments from low light to high light conditions resulted in strong PSII photoinhibition and revealed the distinct light-induced activation of psbA translation, which was further confirmed by reciprocal shift experiments. In low-light-to-high-light shift experiments, as well as reciprocal treatments, the expression of all other chloroplast genes remained virtually unaltered. Altogether, our data suggest that low light-acclimated plants upregulate the translation of a single chloroplast gene, psbA, during acclimation to high light. Our results indicate that psbA translation activation occurs already at moderate light intensities. Possible reasons for the otherwise mild effects of light intensity changes on gene expression in differentiated chloroplasts are discussed.